Avaliação da Atividade Anticâncer do Inibidor de Peptidase Inga laurina Trypsin Inhibitor (ILTI) - Queisielle Magalhães Carvalho de Souza (2022)
Kunitz family peptidase inhibitors have several anticancer mechanisms of action. Inga laurina Trypsin inhibitor (ILTI) is known for its insecticidal, fungicidal and antibiofilm activities. Recently, ILTI was produced by heterologous expression and exhibited potential in vitro anticancer activity. However, the anticancer mechanism of action has not been elucidated. In order to increase the available knowledge about the anticancer action of plant peptidase inhibitors from the Kunitz family, we propose to investigate the anticancer properties of ILTI in a leukemia model. The screening test was performed with the tetrazolium salt MTT using the leukemic strains KG-1, Kasumi and K-562 exposed to ILTI at 0.5 and 5 μM for 24 h. The test with resazurin was performed on the Raji, CCRF-CEM, KG-1, Kasumi-1 and K-562 strains, exposed to ILTI between 0.1 and 0.5 μM, in 24 h, to obtain the curves of cytotoxicity. The anticancer mechanism of action of ILTI was verified in the model of chronic myeloid leukemia K-562 by flow cytometry. ILTI was used at 0.07 μM, concentration corresponding to the IC50 obtained in the cytotoxicity assay with propidium iodide (PI), in 24 h. The type of cell death was verified using annexin-V-FITC/PI double labeling after 24 h of ILTI exposure. The caspase-3 activation assay was also performed with PE Rabbit Anti-Active Caspase-3 antibody after 12 h and 24 h. The cell cycle was analyzed using PI labeling after 24 h. ILTI was cytotoxic to Raji, CCRF-CEM, KG-1, Kasumi-1 and K-562 strains. K-562 leukemic cells treated with ILTI underwent apoptosis process mediated by caspase-3 activation. Apparently, apoptosis was the main pathway of activated death, since there was insignificant increase in death by necrosis. It is possible that ILTI-induced apoptosis is involved with cell cycle arrest in the G2/M phase observed in K-562 cells. Future experiments should include activation of caspase-9, release of cytochrome c and loss of mitochondrial potential, to corroborate current results and bring a better understanding of the anticancer activity of ILTI. Keywords: leukemias, chronic myeloid leukemia, inhibitors, apoptosis.